2016
DOI: 10.1002/anie.201509643
|View full text |Cite
|
Sign up to set email alerts
|

A Mononuclear CoII Coordination Complex Locked in a Confined Space and Acting as an Electrochemical Water‐Oxidation Catalyst: A “Ship‐in‐a‐Bottle” Approach

Abstract: Preparing efficient and robust water oxidation catalyst (WOC) with inexpensive materials remains a crucial challenge in artificial photosynthesis and for renewable energy. Existing heterogeneous WOCs are mostly metal oxides/hydroxides immobilized on solid supports. Herein we report a newly synthesized and structurally characterized metal-organic hybrid compound [{Co3 (μ3 -OH)(BTB)2(dpe)2} {Co(H2O)4(DMF)2}0.5]n ⋅n H2O(Co-WOC-1) as an effective and stable water-oxidation electrocatalyst in an alkaline medium. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 47 publications
9
96
0
Order By: Relevance
“…The electrochemical impedance spectrum (EIS) analysis, and electrochemical double-layer capacitance (C dl ) test, further confirmed that the function of Fe 3+ in enhancing OER activity is through decreasing the charge transfer impedance and enlarging the catalytically active surface area in comparison Adv. [12,17,[24][25][26][27][28][29][30] Importantly, the Fe, Co co-contained Fe@BIF-91 electrocatalyst, showed enhanced OER activity greater than Fe-containing-only Fe@BIF-89. 2019, 6, 1801920 with BIF-91 ( Figures S6 and S7, Supporting Information).…”
Section: Oxygen Evolution Reactionmentioning
confidence: 97%
“…The electrochemical impedance spectrum (EIS) analysis, and electrochemical double-layer capacitance (C dl ) test, further confirmed that the function of Fe 3+ in enhancing OER activity is through decreasing the charge transfer impedance and enlarging the catalytically active surface area in comparison Adv. [12,17,[24][25][26][27][28][29][30] Importantly, the Fe, Co co-contained Fe@BIF-91 electrocatalyst, showed enhanced OER activity greater than Fe-containing-only Fe@BIF-89. 2019, 6, 1801920 with BIF-91 ( Figures S6 and S7, Supporting Information).…”
Section: Oxygen Evolution Reactionmentioning
confidence: 97%
“…Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) werep erformedi n0 .1 m KOH solution at pH 13 with as tandard three-electrode system.T he CV and LSV were performed while the working electrode was rotating at a rotationr ate of 1600 rpm in order to keep au niform concentration around the working electrode and also to prevent the accumulation of O 2 bubbles.T he detailed experimental procedure and calculations for the electrochemical analysis are given in Experimental Section. [35,47] The probable mechanism for TA-MOF and NH 2 TA-MOF mediated water oxidation is outlined in Figure S14. The CV analysis of Ni MOFs reveals an apparent quasireversible oxidation peak at peak potentialo f1 .40 V versusR HE which corresponds to the oxidation process of Ni 2 + to Ni 3 + (Ni II /Ni III ) ( Figure 3a).…”
Section: Oxygene Volution Reaction (Oer) Studymentioning
confidence: 99%
“…[8][9][10][11] Amongt he TMOs, cobalt-based spinel oxides have been shown as outstanding OER electrocatalysts. [28][29][30][31][32][33][34][35] However,o nly af ew examples of MOFs that are directlyu tilized as active OER catalysts have been reported to date. [14][15][16][17] MOFs have attracted immense attention during the past few years fort heir fascinating, diverse structural architectures,a nd more importantly for their novel intrinsic and extrinsic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Thus, cobalt oxygen-evolution catalysts (Co-OECs) have received immense attentioni nr ecent years. [19][20][21][22][23][24] Among Co-OECs, CoOx has extensively been studied as an efficient catalyst that works over aw ide pH range. [25] Co 3 O 4 has also been described as aC o-OEC.…”
Section: Introductionmentioning
confidence: 99%